UTILIZATION OF PALM OIL SOLID WASTE AS ORGANIC FERTILIZER TO SUBSTITUTE COMBINED INORGANIC FERTILIZER WITH PLANTING DISTANCE TO IMPROVE THE GROWTH AND PRODUCTION OF SOYBEAN PLANTS (Glycine max L.) - Sri Rahayu; Muhammad Rizwan; Rahmad Setia Budi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of organic compost fertilizer and planting distance on the growth and production of soybean plants. This study uses a randomized block design (RBD) factorial with two treatment factors, namely compost fertilizer and planting distance. The first factor, compost fertilizer, consists of five levels: S0 = No treatment, S1 = 75% inorganic NPK fertilizer + 25% organic compost fertilizer, S2 = 50% inorganic NPK fertilizer + 50% organic compost fertilizer, S3 = 25% inorganic NPK fertilizer + 75% compost organic fertilizer, S4 = 100% compost organic fertilizer. The second factor is planting distance, which consists of three levels: J1 = 20 cm x 30 cm planting distance, J2 = 20 cm x 40 cm planting distance, J3 = 25 cm x 40 cm planting distance. The observed parameters were plant height, leaf chlorophyll content, root nodule count, pod count, filled pod count, empty pod count, weight of 100 seeds, seed yield per plot, wet pod weight, and dry pod weight. The results of the study indicate that the application of compost fertilizer has a significant effect on soybean plant height, leaf chlorophyll content, and root nodule count. Planting distance has a significant effect on empty pod weight, 100-seed weight, and dry pod weight. The interaction between compost fertilizer and plant spacing had no significant effect on plant height, leaf chlorophyll content, root nodule number, pod number, filled pod number, empty pod number, 100-seed weight, seed yield per plot, wet husk weight, and dry husk weight.